Thermal effect of mass concrete structures in the tropics: Experimental, modelling and parametric studies. Issue 1 (1st January 2017) - Abeka, Herbert; Agyeman, Stephen; Adom-Asamoah, Mark
Abstract: This paper is an experimental investigation and analytical simulation of thermal effects on mass concrete structures in the tropics. A study of the temperature rise of a 1.1 m × 1.1 m × 1.1 m experimental mass concrete block, well instrumented with thermocouples to monitor the temperatures distribution was performed. A validated finite element model was used to predict the temperature development of the hydrating experimental mass concrete block. Thermal stress analysis was performed to give an estimate of stresses induced by the thermal gradient of the concrete block section and the crack index was used to quantify the probability of thermal cracking. A parametric study on the effect of the surface area to volume ratio (SVR) of mass concrete was performed to quantify the maximum allowable thermal gradient as well as the induced thermal stresses that may cause thermal cracks. For SVR less than 0.36, thermal cracks may occur at early ages of concrete strength development in the tropics.